PENERAPAN SUPERVISI AKADEMIK MELALUI E-PERSONAL KINERJA DI PMM DAPAT MENUMBUH KEMBANGKAN KOMPETENSI GURU DI SDN BEJI 02 - Sulistyorini, Emmelia Maria; Kurniawati, Zulianti Lisa; Soedjono, Soedjono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Academic supervision is a series of activities to help teachers develop their abilities in managing the learning process to achieve learning goals. This research aims to find out how planning, implementation, follow-up planning and obstacles to academic supervision by school principals improve teacher competency at SD Negeri Beji 02. This research uses a descriptive method with a qualitative approach. Data collection techniques using interview, observation and documentation study methods. The research subjects were school principals, class 1-6 teachers. Data were analyzed using reduction, presentation and conclusion techniques. The Ministry of Education and Culture, Research and Technology provides the Independent Teaching Platform (PMM) which allows teachers to develop themselves and broaden their horizons about education. PMM, which has been provided by the government as a tool for implementing the independent curriculum, has features that assist school principals in carrying out academic supervision and assist teachers in developing their competencies. The results of the implementation of academic supervision will later be integrated directly with the performance platform, especially for teachers who have civil servant and PPPK status. The implementation of academic supervision through e-Personal Performance at PMM, although it offers many benefits, still faces several obstacles, one of which is a lack of IT mastery which prevents senior teachers from operating e-Personal Performance at PMM, so there is a need for regular training and mentoring to improve teachers' abilities in using e-Personal Performance.